The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1149/1945-7111/ac7829
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Nitrogen-Doped and Sulfur-Doped Multilayer Graphene for Use in Bifunctional Oxygen Electrodes

Abstract: Nitrogen-doped and sulfur-doped mechanochemically synthesized multilayer graphene (N-doped and S-doped MSMG) were prepared by planetary ball-milling, and they were used in bifunctional gas diffusion electrodes (GDEs) for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Graphite, melamine, and elemental sulfur were used as raw materials. The surface area-normalized linear sweep voltammograms revealed that the N-doped and S-doped MSMG have higher intrinsic ORR/OER activity than the undope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
(75 reference statements)
0
0
0
Order By: Relevance
“…The mechanochemical or mechanochemically induced N-doping of carbon is a productive, simple, cheap, and, most importantly, environmentally acceptable method. This method makes it possible to obtain carbon materials with a high degree of doping up to ∼30 atom % of nitrogen. Studies conducted by various research groups have shown that the materials obtained in this way are capable of exhibiting high functional characteristics in different fields, such as anodes for sodium- and lithium-ion batteries, , supercapacitor electrodes, electrocatalysts for oxygen reduction, , among others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanochemical or mechanochemically induced N-doping of carbon is a productive, simple, cheap, and, most importantly, environmentally acceptable method. This method makes it possible to obtain carbon materials with a high degree of doping up to ∼30 atom % of nitrogen. Studies conducted by various research groups have shown that the materials obtained in this way are capable of exhibiting high functional characteristics in different fields, such as anodes for sodium- and lithium-ion batteries, , supercapacitor electrodes, electrocatalysts for oxygen reduction, , among others.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only a limited number of publications are devoted to the mechanochemical doping of carbon materials with nitrogen atoms. Sources of nitrogen atoms during mechanochemical processing can be substances, such as melamine, ,,, urea, ammonium fluoride, ammonia, , and nitrogen gas. , In some cases, doping occurs directly in the mill, ,,,,, while in others, it is carried out during the subsequent processing of mechanochemically activated carbon materials. , From a practical perspective, doping carbon materials with nitrogen atoms directly in a mill in a nitrogen atmosphere is of undoubted interest due to the nontoxicity of the gas itself, its wide distribution, and the simplicity of the method. However, nitrogen gas is a very inert substance, and to achieve doping, it is necessary to carry out a prolonged mechanochemical treatment, which in some cases reaches several days. , …”
Section: Introductionmentioning
confidence: 99%